El proceso de aprendizaje del área de Lengua y Literatura en la Unidad Educativa del milenio Santiago de Píllaro, provincia de Tungurahua, período académico 2021– 2022 - Quishpe Quishpe, Deisy Jackelinn (2022)
The learning of language and literature has the responsibility of guiding the development of cognitive skills and communication skills through reading and writing. In the Educational Unit of the Millennium Santiago de Pillaro it has been possible to identify the disinterest in reading on the part of the students, reading is little used, they take their practice as a punishment, reading in the students is slow and syllabic, they omit signs punctuation when reading aloud, punctuation sounds are substituted and poor reading comprehension is observed. The objective of this research is to strengthen the learning process in the area of Language and Literature through methodological strategies based on reading comprehension in the Educational Unit of the Millennium Santiago de Píllaro, year 2021-2022. The methodology used is a qualitative, interpretive approach, with a design based on content analysis, to contrast the learning elements of reading comprehension in a real environment such as the classroom. The techniques used were the observation and the interview which allowed to collect data inherent to the variables, their instrument was the observation guide and the interview guide that allowed to collect information from representative people of the educational community. The result achieved is the construction of a methodological guide to improve learning through the development of reading comprehension, based on readings extracted from seventh-year texts. As a result, the teachers applied the proposal in order to develop reading comprehension in the child.